Excessive Lipolysis and Inflammatory Response in Adipose Tissue Are Associated with Elevated Serum Growth Hormone in Dairy Cows with Clinical Ketosis - Xinxing Gao (22653201) (2025)
Supplemental Table 1. Basic description of the control and clinical ketotic cows Supplemental Table 2. Ingredients and chemical compositions of the diets fed to dairy cows during the experiment Supplemental Table 3. The primer sequences (For, forward; Rev, reverse) Supplemental Table 4. Effects of different concentrationsof growth hormonetreatment (0, 5, 10 or 15 ng/mL) on glycerol content in supernatant and triglyceride content in bovine adipocytes Supplemental Table 5. Effects of different timesof growth hormonetreatment (0, 4, 8 or 12 h) on glycerol content in supernatant and triglyceride content in bovine adipocytes Supplemental Table 6. Effects of different concentrationsof growth hormonetreatment (0, 5, 10 or 15 ng/mL) onphosphorylation levels of IκBα and NF-κBand relative protein abundance of IκBα in bovine adipocytes Supplemental Table 7. Effects of different concentrationsof growth hormonetreatment (0, 5, 10 or 15 ng/mL) on mRNA abundance of TNFA, NLRP3, IL18, CASP1 and IL1B and the activity of caspase 1 in bovine adipocytes Supplemental Table 8. Effects of different timesof growth hormonetreatment (0, 4, 8 or 12 h) on phosphorylation levels of IκBα and NF-κBand relative protein abundance of IκBα in bovine adipocytes Supplemental Table 9. Effects of different timesof growth hormonetreatment (0, 4, 8 or 12 h) on mRNA abundance of TNFA, NLRP3, IL18, CASP1 and IL1B and the activity of caspase 1 in bovine adipocytes